Research progress of behavioral variant frontotemporal dementia - Xiao-hua GU; Jun XU (Chinese Journal of Contemporary Neurology and Neurosurgery, 2015)
There is no epidemiological data of frontotemporal dementia (FTD) in China. The application of updated diagnostic criteria, publishing of frontotemporal lobar degeneration (FTLD) consensus in China, development of multimodal imaging and biomarkers promote the clinical understanding on behavioral variant frontotemporal dementia (bvFTD). There is still no drugs treating FTD approved by U.S. Food and Drug Administration (FDA). Multidisciplinary intervention may delay the progression of bvFTD.   DOI: 10.3969/j.issn.1672-6731.2015.07.006